A Different Third R: Radical Math - Frankenstein, Marilyn (Radical Teacher, 2014)
Mathematical literacy is more than the ability to calculate. It is the ability to reason quantitatively, the ability to use numbers to clarify issues and to support or refute opinions. Yet the proliferation of arithmetic courses at the college level is evidence that people are not learning even basic computation skills in school. Too many adults cannot use numbers effectively in their daily lives. This article will briefly examine the causes of this situation and will outline a basic arithmetic course that not only teaches adults math effectively, but raises their political consciousness and empowers them to analyze and question the status quo, and to fight back.